The universal handset. - Koch, P.
Software-defined radio can let cellphones speak Wi-Fi, 3G, WiMax, and more. In the new millennium, SDR has spread from the battlefield to the commercial arena. Wireless service providers, in particular, have begun using it in the transceivers in cellphone base stations, allowing the same hardware to handle different cellular protocols. Next, SDR will spread to sets that fit in the palm of your hand. A mobile software radio that could communicate in all of these ways would, of course, be invaluable. Up until now, SDR technology worked only in applications that didn't need to be small in size or frugal in power consumption. New technology should, however, overcome these constraints. Indeed, within the next year or so, you can expect to see people moth- balling their old cellphones in favor of new software- defined handsets.
Keywords: 3G communication; Wi-Fi.; WiMax; Cellphone base station; Cellular protocol; Mobile software radio; Transceiver; Universal handset; Wireless service provider